Prevalence and Predictors of Screen Time Exposure in Young Children: A Descriptive, Facility Based Study - Ashutosh Paldiwal; Pritam Kabra; Umesh Kawalkar; Amar Prakash Mankar; Mahesh Puri; Aditi Rathod (Preventive Medicine: Research & Reviews, 2024)
Background: Excessive screen time exposure amongst children has become a global concern due to its detrimental effects on health and development. Understanding the prevalence and associated risk factors is crucial for designing effective interventions. This study aimed to estimate screen exposure time and identify associated risk factors amongst children aged 6 months–6 years in Akola district, India. Materials and Methods: A descriptive facility based study was conducted in Akola district, utilising data collected from two outpatient departments. Data were collected through interviews with mothers using a pre-designed questionnaire. Sociodemographic factors and screen time habits were assessed. Statistical analyses, including multivariate regression, were performed to identify significant predictors of screen exposure time. Results: Of the 417 children included in the study, 53.7% had excess screen exposure, with an average screen time of 1.6 h. Infants under 1 year had notably high exposure rates (95.1%). Maternal and paternal education, maternal occupation and child’s behaviour (throwing tantrums) were significantly associated with screen exposure time. Conclusions: The findings highlight the urgent need for public health interventions to address excessive screen time amongst young children in Akola district of India. Efforts should focus on raising parental awareness, promoting healthier screen time practices and encouraging outdoor activities. Further research is recommended to assess the impact of interventions and the evolving screen time patterns, particularly in light of the COVID-19 pandemic.